Cooking Fuel Choice, Indoor Air Quality and Child Mortality in India - Arnab K. Basu; Tsenguunjav Byambasuren; Nancy H. Chau; Neha Khanna (Global Labor Organization (GLO), 2020)
Indoor air pollution (IAP)–predominantly from the use of solid fuel for cooking– is a global health threat, particularly for women and young children, and one of the leading causes of infant deaths worldwide in developing countries. We estimate the causal effect of cooking fuel choice on infant mortality in India, focusing on children under five years of age using pooled cross-sectional data from the National Family Health Survey (NFHS) over the period 1992–2016. To address the potential endogeneity in the relationship between fuel choice and mortality, we instrument for cooking fuel choice using a speed of change in forest cover and ownership status of agricultural land, which induce significant variations in fuel type. We find that cooking fuel choice has a statistically significant impact on under-five and neonatal mortality, raising the mortality risk by 4.9 percent. We also find that the past literature has overestimated the association between under-five mortality and polluting fuel use by about 0.6 percentage points or equivalently, 152,000 deaths per year nationally. Our result is robust to a set of alternative specifications with the inclusion of various controls and different estimation strategies.
Keywords: I18; N35; Q53; 330; cooking fuel; indoor air pollution; infant mortality; India